Group portrait of the attendees of the 28th Conference of the California Chapter #4 of the National Association of Postmasters of the United States - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the 28th Conference of the California Chapter #4 of the National Association of Postmasters of the United States, held May 20-22, 1952 in San Jose, California.